Multi-functional carbon nanotube paper for solar water evaporation combined with electricity generation and storage. (1st August 2021) - Duan, Yimin; Weng, Mingcen; Zhang, Wei; Qian, Yongqiang; Luo, Zhiling; Chen, Luzhuo
Graphical abstract: Highlights: Various carbon nanotube-based devices are developed for solar energy utilization. The water evaporation system can generate freshwater (1.28 kg m −2 h −1 ). The solar-thermoelectric system can output a voltage and charge a cellphone. The supercapacitor performs an areal specific capacitance of 19.6 mF cm −2 . The hybrid energy system can produce freshwater, generate and store electric power. Abstract: Nowadays, multi-functional systems driven by solar energy have been explored to alleviate the crisis of energy and freshwater scarcity. However, it remains a great challenge to integrate multi-functions into one hybrid system with a monolithic material, which can harvest, convert and store solar energy synergistically. Here, we firstly propose a multi-functional carbon nanotube paper, which starts from a material level to solve these problems. The carbon nanotube paper is fabricated by vacuum filtration. It exhibits high efficiency of solar-thermal conversion. Secondly, three types of energy conversion/storage systems (e.g., solar-thermal evaporation system, solar-thermoelectric generation system, and supercapacitor) are constructed based on the carbon nanotube paper, which extend the research to a device level. The solar-thermal evaporation system shows an evaporation rate of 1.28 kg m -2 h −1 under simulated sunlight irradiation of 1 kW m −2 . The solar-thermoelectric generation system demonstrates a stable electric power generation with an output voltage of 100 mV under light irradiation of 1 kW m −2 . The supercapacitors perform the energy storage function with an areal specific capacitance of 19.6 mF cm −2 . These devices and systems can be used in freshwater generation (0.84 kg m -2 h −1, sunlight irradiation of 1 kW m −2 ), water purification/desalination (inorganic ions rejection larger than 99.9%) and portable solar charging system (maximum output voltage of 5 V). Finally, a hybrid energy system is innovatively proposed from the system level to simultaneously produce freshwater, generate and store electric power. Through the synergetic coupling of solar conversion and storage technologies, the hybrid energy system can supply sustainable freshwater and electricity for remote areas in daily life, highlighting the superiority of multi-energy (thermal energy, electrical energy, and electrochemical energy) complementary.